Characteristics of Teratomas Regenerated in Vitro from Octopine-Type Crown Gall - Owens, Lowell D. (1982)
Crown galls induced by infection of tobacco plants with Agrobacterium tumefaciens strain C58-Cl(pTiB6S3) were excised and cultured in vitro. After about one year of culture on medium-lacking phytohormones, two noncloned lines spontaneously formed shoots. Leaf explants from shoots of tumor-line T5 were capable of growing on hormone-free medium, and the resulting mixture of organized and unorganized tissue synthesized octopine. Detached leaves from T5 shoots also synthesized octopine. These results establish that shoots from this octopine-type tumor contain transformed cells and are true crown-gall teratomas.